GLOBAL CRIME PREVENTION - STANCU, Adriana-Iuliana; AGHENIȚEI, Mihaela (International Journal of Legal and Social Order, 2022)
Crime has risen dramatically in recent decades and its costs have followed. States are spending ever-increasing amounts on health and property, as well as on police, investigative procedures, courts, and prisons. According to a recent observation, crime control absorbs a considerable percentage of the gross national product (GNP) in developed countries and much higher in less developed countries. However, these expenditures have had relatively little impact on the crime rate and the rehabilitation of criminals, with the relatively high number of recidivists increasing exponentially. As crime resists efforts to combat it, the interest of legal experts has gradually shifted to innovative methods of prevention rather than punishment. Several studies have shown that crime prevention can significantly reduce the number of crimes, as well as reduce their costs.